Availability of heavy metal concentration in soil around the oil palm (elaeis guineensis) plantation / Rubaiyah Alias - Alias, Rubaiyah (Faculty of Applied Sciences, 2017)
Four heavy metals (Cu, Zn, Pb and Ni) in nine different soil sampling point at oil palm (Elaeis guineensis) plantation were determined by Inductively Coupled Plasma - Optical Emission Spectrometry after wet digestion. This study focus for a number of heavy metals (Cu, Zn, Pb and Ni) that most commonly found at contaminated sites. The ranges of element concentrations for copper, zinc, lead and nickel were 0.76 - 2.00, 0.19 - 1.58, 0.07 - 0.22, and 0.01 - 0.05 mg/kg respectively. Copper content was higher than other metals in all soil samples. The concentration of heavy metals in soil show the following decreasing trend: Cu > Zn > Pb > Ni. All of the metal content level were below than permissible limit that recommended by World Health Organization. The Contamination Factor (CF) value was less than 6 for all heavy metal in nine different soil samples that supposedly not higher contaminated. All soil samples had goo accumulation index (Igeo) less than 2 that consider as uncontaminated. This generally indicate that the soil at oil palm plantation not totally consider as toxicity.